PERAN SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG PENGAMBILAN KEPUTUSAN PADA MANAJEMEN PENDIDIKAN TINGGI - Firdaus, Ivan Taopik (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
This article discusses the strategic role of Management Information Systems (MIS) in supporting decision-making processes in higher education management. In the digital era, higher education institutions face complex governance processes that require integrated and responsive information systems. Using a literature review approach with descriptive qualitative methods, this article examines how MIS is used in managing academic, financial, and human resource data to support evidence-based decision-making. The study results indicate that MIS can improve the efficiency and effectiveness of institutional management, but its implementation still faces challenges such as limited human resources, organizational cultural resistance, and a lack of system integration. This article recommends strengthening a data-driven work culture, training human resources, and supporting institutional policies as strategic steps to optimize the use of MIS in higher education